From crisis to stability: A case series on terlipressin in managing upper gastrointestinal bleeding in chronic liver disease - Geetha, Karra; Sripriya, Atchula; Devi, Kandi Sandhya; Shishla, Madhavaneni; Rao, T Rama (Indian Journal of Case Reports, 2025)
Upper gastrointestinal bleeding (UGIB) is a severe complication of chronic liver disease (CLD) requiring prompt intervention to prevent further morbidity. Terlipressin, a vasopressin analog, is widely employed to stabilize hemodynamics and control variceal hemorrhage. This case series examines the effectiveness of terlipressin in managing UGIB in three patients with CLD. In two cases, the timely administration of terlipressin led to significant clinical improvements, including stabilization of hemodynamic parameters, reduced bleeding episodes, and shorter hospital stays. However, a delay in terlipressin administration in the third case resulted in prolonged hospitalization and delayed recovery, necessitating additional supportive measures. These findings highlight the critical role of early terlipressin therapy in improving clinical outcomes in patients with CLD presenting with UGIB.